Human extrastriate visual cortex and the perception of faces, words, numbers, and colors. - Allison, T; McCarthy, G; Nobre, A; Puce, A; Belger, A (1994)
Electrophysiological correlates of the processing of visual information were studied in epileptic patients with electrodes chronically implanted on the surface of striate and extrastriate cortex. In separate experiments patients viewed faces, letter strings (words and non-words), numbers, and control stimuli. A negative potential, N200, was evoked by faces, letter strings, and numbers, but not by the control stimuli. N200 was recorded bilaterally from discrete regions of the fusiform and inferior temporal gyri. These category-specific face, letter-string, and number "modules" vary in location. In most cases there was no overlap in the location of face and letter-string modules, suggesting a mosaic of functionally discrete regions. In some cases letter-string and number N200s were recorded from the same location, suggesting that these modules may be less spatially and functionally discrete. Face N200-like potentials can be recorded from temporal scalp, allowing the possibility of studying early face processing in normal subjects. Longer-latency face-specific potentials were recorded from the inferior surface of the anterior temporal lobe. Potentials evoked by colored checkerboards were recorded from a region of the fusiform gyrus posterior to the fusiform region from which category-specific N200s were recorded. These results suggest that there are several processing streams in inferior extrastriate cortex. In addition to object recognition systems previously proposed for faces and words, our preliminary results suggest a separate system dealing with numbers. Postulated systems dealing with larger manipulable objects and animals have not been detected.